KONTRIBUSI NILAI-NILAI HINDU TERHADAP PENGEMBANGAN SOCIAL-EMOTIONAL WELL-BEING SISWA - I Wayan Rudiarta; Nyoman Dantes; I Made Tegeh; Ni Made Ayu Dwi Oktaviani (Institut Agama Hindu Negeri Gde Pudja Mataram, 2026)
The well-being and mental health of students are becoming a global issue receiving increasing attention in education, as students face greater academic, social, and emotional demands. This research aims to conduct a critical exploration and analysis of the contribution of Hindu values to students' social-emotional well-being. This study uses a qualitative approach, grounded in a literature review, analyzing primary sources such as Hindu scriptures namely the Bhagavad Gita and the Sarasamuccaya, books, scientific articles, and other references relevant to education, mental health, and social-emotional learning. The results of the study show that Hindu values, especially Tri Kaya Parisudha, Tat Tvam Asi, Tri Guna, and Tri Hita Karana, align closely with the five core competencies of SEL according to CASEL: self-awareness, emotional control, social awareness, relational skills, and responsible decision-making. Furthermore, Hindu values not only support students' psychosocial development but also enrich the SEL framework with spiritual, ethical, and cultural dimensions that play an important role in building students' emotional regulation, empathy, mental balance, and harmony in their social relations. The implementation of Hindu values in Hindu Religious Education through a reflective, contextual, and experiential approach has the potential to strengthen students' social-emotional well-being holistically and sustainably. This research emphasizes the importance of integrating local religious and cultural values in the development of mental health-oriented education and character formation of 21st-century students.